(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study provides a comprehensive framework for energy monitoring and control in smart home settings via wireless sensor networks (WSNs). The use of ZigBee guarantees minimum power usage, extensive scalability for many home products, and reliable transmission of energy consumption data. The concept consists of three primary modules: information acquisition via wireless sensors, data processing via a central gateway, and information presentation through a user-friendly web/mobile interface. Power consumption is quantified using Hall-effect sensors, in conjunction with ADC and microcontroller units, which also provide remote ON/OFF control of appliances from the database. The gathered data is kept in a PostgreSQL database and retrieved in real-time for user engagement and system assessment. Performance testing indicates exceptional accuracy (up to 99.3%), minimal latency (less 1 second), and reliable stability over diverse electrical loads. The proposed system offers fundamental functionalities like consumption monitoring and appliance management, with the ability to expand into sophisticated services such as tariff-based suggestions and context-aware automation. The framework aims to save energy, enhance user empowerment, and maximize home automation.